METHODICAL PRINCIPLES OF CREATING A GEOINFORMATION DATABASE FOR TERRITORIAL COMMUNITIES - Stupen, Р.; Ryzhok, З.; Stupen, О. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2023)
It is established that creation of a geoinformation database for territorial communities will provide visualization, operational access, administration and updating of urban planning documentation, which includes general plans and detailed plans of territories, topographic plans, orthophoto plans, as well as a comprehensive plan for spatial development of the community area. It has been studied that the basic geospatial data are the publicly available geospatial data that create a unified digital coordinate-spatial basis for production, integration and implementation of other activities with various geospatial data. The research describes the structure of a geoinformation database for creating the urban planning documentation, including a set of layers for the class of spatial objects, i.e. "planning_elements" in the geoinformation system QGIS. The structure of attributes for the class of spatial objects "hromada" in the geodatabase of the set of classes of objects "planning_elements" is presented. The authors of the research presents result of creating attribute data for the class of spatial objects "hromada" in the geodatabase for creation of the urban planning documentation in the geoinformation system QGIS at the local level. A vector layer for the spatial object "hromada" was created with a set of characteristics (attributes) based on the example of Zhovtantsi territorial community in Lviv region. It is proven that the use of geoinformation system QGIS in the field of community land resource management and creation of the urban planning documentation totally ensures creating geospatial data in the USK-2000 State Geodetic Reference System of Coordinates.